Recent Advances in Image-Guided Radiotherapy for Head and Neck Carcinoma. (29th July 2009) - Nath, Sameer K.; Simpson, Daniel R.; Rose, Brent S.; Sandhu, Ajay P.
Abstract : Radiotherapy has a well-established role in the management of head and neck cancers. Over the past decade, a variety of new imaging modalities have been incorporated into the radiotherapy planning and delivery process. These technologies are collectively referred to as image-guided radiotherapy and may lead to significant gains in tumor control and radiation side effect profiles. In the following review, these techniques as they are applied to head and neck cancer patients are described, and clinical studies analyzing their use in target delineation, patient positioning, and adaptive radiotherapy are highlighted. Finally, we conclude with a brief discussion of potential areas of further radiotherapy advancement.